Faktor-Faktor Yang Berhubungan dengan Pemberian Asi Eksklusif di Dusun Tanjung Tahun 2024 - Miftahurrahmi Miftahurrahmi (Jurnal Medical Laboratory, 2024)
The basic model for the formation of a quality human being begins when the baby is in the womb accompanied by the provision of breast milk (ASI) from an early age, especially exclusive breastfeeding, namely giving breast milk alone without anything else to the baby from birth until six months old. Every parent definitely wants to have healthy and intelligent children. Parents do many things to achieve this goal. Starting from often listening to classical music, taking vitamins to giving formula milk containing AA and DHA which is believed to increase children's intelligence, but unfortunately, many mothers in Indonesia do not give breast milk to their babies, even though by giving breast milk their health and intelligence the baby is guaranteed. This research aims to determine the factors associated with exclusive breastfeeding in Tanjung Hamlet. The type of research is analytical with a cross sectional design. The population in this study were all breastfeeding mothers in Tanjung Hamlet, totaling 86 people with a sample of 86 people. The sampling method is total sampling. The research variables are knowledge, education and age. The data collection tool is a questionnaire. Data analysis in this research is univariate and bivariate analysis. The research results showed that the majority of respondents had low knowledge about exclusive breastfeeding, namely 76.7%. Most of the respondents had low education, namely 68.9%. Most of the respondents were >39 years old, namely 77.8% and the majority of respondents did not provide exclusive breastfeeding, namely 93.3%. Based on statistical tests, it was concluded that there was a relationship between knowledge and exclusive breastfeeding, namely 0.000, there was a relationship between education and exclusive breastfeeding, namely 0.002 and there was a relationship between age and exclusive breastfeeding, namely 0.002.